FOSTERING PROFESSIONAL COMPETENCE IN HIGHER MEDICAL EDUCATION - Popova, I.B.; Yemchenko, Ya.O.; Vasilyeva, K.V. (Актуальні проблеми сучасної медицини: Вісник Української медичної стоматологічної академії, 2025)
Relevance. The competency-based approach, originating from behavioral theory, has evolved into a foundational element of modern education and is now the dominant paradigm in both higher and postgraduate learning. This approach emphasizes aligning educational programs with the practical needs and expected outcomes for graduates. In the context of medical education, the growing interest of researchers in issues surrounding professional training is driven by several pressing contradictions. These include the gap between traditional methods used in medical colleges and the need to enhance the effectiveness of professional preparation, the current limitations of training models, and the urgency of adopting more dynamic, interactive, and learner-centered strategies. There is a clear need to foster students’ cognitive engagement, promote autonomous learning, and establish subject–subject relationships between instructors and learners. Furthermore, the tension between the increasing volume of professionally significant information, limited instructional time, and the necessity for comprehensive, meaningful education of future specialists underscores the relevance of this study. Objective. To examine the pedagogical challenges related to the formation of professional competence in future physicians within higher education institutions and to outline the theoretical foundations for addressing this issue. Materials and Methods. The study employed a qualitative methodological framework grounded in theoretical analysis and generalization. A wide range of contemporary scientific and pedagogical literature was reviewed to identify key concepts and trends in competency-based medical education. The analysis focused on models of professional competence development, the integration of soft and hard skills, and the pedagogical strategies that support meaningful, practice-oriented learning. The findings were further contextualized through reflective examination of educational practices in selected medical departments, with attention to how competency-based principles are operationalized in real teaching environments. Results. The competency-based approach reflects the content of education, which is not reduced to knowledgeoriented elements, but rather to acquiring integrated experience in solving life problems, performing basic functions, social roles and demonstrating competence. Mastering the components of professional competence enables specialists to possess a set of competencies for the effective provision of medical care. The higher the level of competence, the broader the competence of the doctor. Competence is not only the result of education, it cannot be deepened without personal experience, and the integration of these elements is the path to professionalism. In addition, if effective health care is considered a matter of national security, then to increase its effectiveness it is necessary to urgently implement programs for preand postgraduate education of doctors in the field of understanding modern clinical information.